The need and validation of HER2 positive Breast cancer spheroid models for antibody drug conjugate research and development - Gustafsson, Joakim (My University, 2025)
Antibody drug conjugates (ADCs) are a relatively new drug modality, where instead of using antibodies to inhibit the function of overexpressed oncogenic tyrosine kinase receptors on the cell surface, ADCs can target any protein on the cell membrane and via internalization of the target protein, deliver a cytotoxic payload into the cancer cell. Enhertu (T-DXd) and Kadcyla (T-DM1) are FDA and EMA approved ADCs for the treatment of HER2 positive breast cancer. Enhertu has been shown to have better responses in the clinics compared to Kadcyla. However, similar difference in efficacy, has not been able to be demonstrated in the standard dose-response studies with in vitro monolayer (2D) cell cultures. It is known that ADCs suffer from weak penetration into the tumor tissue in patients. The efficacy of Enhertu is likely due to the high antibody to drug ratio and the bystander effect of the payload Deruxtecan (DXd) compensating for the lower ADC exposure caused by the weak penetration. These characteristics require a three-dimensional (3D) model like a spheroid to observe their advantages. Two HER2+ Breast cancer spheroid models and one HER2-negative spheroid model were developed, and their antibody internalization and ADC cytotoxicity dose-response were studied, and the results were compared to their corresponding 2D results. We found that there were noticeable differences in the cumulative intake of trastuzumab between 2D and 3D culture formats. The HER2+ models showed increased insensitivity to Topoisomerase 1 inhibitors, which lead to a reduced cell killing with T-DXd, DXd and Exatecan. T-MMAF and T-DM1 showed the same relative efficacy ranking across both 2D and 3D culture formats. The 2D culture format with HCC1954 cell line was observed to overestimate the efficacy of all ADCs in comparison to the 3D culture format. Immunofluorescent staining and confocal imaging were successfully conducted to assess the ADC penetration and payload distribution of T-DXd inside a spheroid.
Keywords: Antibody drug conjugate, ADC penetration, Breast cancer, Bystander effect, Confocal imaging, Dose-response, HER2-targeted therapy, Internalization, Spheroid